Peningkatan Keterampilan Berbicara Melalui Model Pembelajaran Listen-Read-Discuss (LRD) Siswa Kelas IV SDN 2 Batuputih Kabupaten Kolaka Utara - Aulia Fajarina Hidayati; Abd. Munir Kondongan; Desy Ayu Andhira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve speaking skills through the Listen-Read-Discuss learning model for class IV students at SDN 2 Batuputih. This research is class action research (Class Action Reasech) which consists of two cycles. Each cycle consists of three meetings. The research procedure includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were 22 grade IV students at SDN 2 Batuputih. Data collection techniques consist of observation, tests, documentation. The instruments used in this research were observation sheets and student assessment sheets. The research results showed that in the first cycle, which was completed individually, of the 22 students, only 12 students met the minimum completion criteria (KKM) or were in the low category. Classically it has not been fulfilled because the average value obtained was 69.3. Meanwhile, in cycle II, out of 22 students, 20 students had fulfilled the KKM and classically had been fulfilled, namely the average score obtained was 81 or was in the good or high category. Based on the results of the research above, it can be concluded that the speaking skills of class IV students at SDN 2 Batuputih through the Listen-Read-Discuss learning model have improved.